2018
DOI: 10.1021/acsomega.8b01490
|View full text |Cite
|
Sign up to set email alerts
|

Development of Novel Solid-State Light-Emitting Materials Based on Pentafluorinated Tolane Fluorophores

Abstract: We herein describe the synthesis of novel pentafluorinated tolane fluorophores, which possess an extended π-conjugated structure with a large molecular dipole moment along the longitudinal axis. We also report a detailed evaluation of both the photophysical and thermal behaviors of these fluorophores. All molecules displayed photoluminescence (PL) characteristics in both the crystalline state and in dilute solutions. The large longitudinal dipole moment induced solvatochromic PL behavior, which switched sensit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 49 publications
0
20
0
Order By: Relevance
“…Since the chemical properties of the chiral and racemic mixtures were the same, typical synthetic procedures and the spectral data only for S-configured S-2a and S-2b are reported below as selected examples. The molecular structures of bistolane 2a and 2b were characterized via spectroscopic analyses, such as 1 H, 13 C, and 19 F NMR spectroscopy; infrared (IR) We subsequently directed our attention toward novel pentafluorinated bistolane-type LELCs with branch structures in their flexible units because the electric or steric effect can induce dynamic changes of molecular dipoles and molecular arrangements in condensed phases ( Figure 1B). Therefore, in this article, we describe the molecular design and synthesis of novel pentafluorinated bistolane-type LELCs carrying flexible units with the branch structure shown in Figure 1b and present detailed evaluations of their LC and PL properties.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Since the chemical properties of the chiral and racemic mixtures were the same, typical synthetic procedures and the spectral data only for S-configured S-2a and S-2b are reported below as selected examples. The molecular structures of bistolane 2a and 2b were characterized via spectroscopic analyses, such as 1 H, 13 C, and 19 F NMR spectroscopy; infrared (IR) We subsequently directed our attention toward novel pentafluorinated bistolane-type LELCs with branch structures in their flexible units because the electric or steric effect can induce dynamic changes of molecular dipoles and molecular arrangements in condensed phases ( Figure 1B). Therefore, in this article, we describe the molecular design and synthesis of novel pentafluorinated bistolane-type LELCs carrying flexible units with the branch structure shown in Figure 1b and present detailed evaluations of their LC and PL properties.…”
Section: Methodsmentioning
confidence: 99%
“…Since the chemical properties of the chiral and racemic mixtures were the same, typical synthetic procedures and the spectral data only for S-configured S-2a and S-2b are reported below as selected examples. The molecular structures of bistolane 2a and 2b were characterized via spectroscopic analyses, such as 1 H, 13 C, and 19 F NMR spectroscopy; infrared (IR) spectroscopy; and HRMS. The NMR spectra indicated that the products were sufficiently pure for the evaluation of their LC and PL properties.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Very recently, extensive research on fluorine‐containing functional materials, such as light‐emitting and liquid‐crystalline materials, has been conducted in our group, leading to the successful development of pentafluorinated diphenylacetylenes ( G ) and 1,2‐bis(phenylethynyl)benzenes ( H ), which exhibit photoluminescence (PL) behavior in both crystalline and dilute solution states (Figure ). During the course of our research, hexafluorocyclopentene derivatives bearing two pentafluorinated diphenylacetylene arms ( I ) have been found to exhibit intense yellow PL with large Stokes shifts in dilute solution.…”
Section: Introductionmentioning
confidence: 99%